Pelanggaran Hukum Terhadap Hak Konsumen oleh Pelaku Usaha Pada Marketplace Dengan Tidak Memberikan Informasi Mengenai Produk Secara Jelas - Ridhan Zhafari, Firdaus (LPPM Universitas Ekasakti Padang, 2024)
The rapid advancements in technology, particularly in the fields of science and technology, have significantly simplified human activities, especially in economic terms. This is evident in the shift towards online transactions, which have become a primary mode for economic activities and meeting daily needs, such as online buying and selling. In today’s globalized era, transactions do not require face-to-face interactions thanks to internet platforms known as marketplaces. These platforms facilitate the exchange between sellers and buyers without direct contact, offering various transactional facilities that enhance user convenience such as multiple payment methods, detailed product categories, delivery options, and a range of seller credentials including official shops and trusted labels. However, while these features provide numerous advantages, there are also inherent risks, such as increased opportunities for fraud since the transactions are not conducted face-to-face. This paper highlights a specific case encountered on the Shopee marketplace involving a misrepresented sale of a book, illustrating a breach of consumer rights as defined by Indonesia's Consumer Protection Law No. 8 of 1999. The principles of consumer protection, which include fairness, balance, and legal certainty, are discussed. These principles are essential for ensuring that consumers are protected from deceptive business practices and receive goods that correspond both in quality and quantity to what is paid for and advertised by the business.